Monodispersed Zerovalent Iron Nanoparticles Decorated Carbon Submicrospheres for Enhanced Removal of DDT from Aqueous Solutions. Issue 41 (7th November 2019) - Kang, Shenghong; Wang, Guozhong; Wang, Zhaoming; Cai, Weiping
Abstract: A simple route is presented to fabricate the nano zero‐valent iron/carbon sphere (nZVI/CSs) composites via Fe 2+ ion‐adsorption and then reduction reaction on the pre‐prepared CSs. The nZVI/CSs composites with monodispersed nZVI particles are successfully fabricated. The monodispersed nZVI particles with 30–50 nm in size are uniformly decorated on the sub‐microsized CSs with about 250 nm in diameter. These nZVI/CSs composites are of enough high specific surface area (about 55.8 m 2 ⋅g −1 ) and good ferromagnetism. Importantly, such nZVI/CSs have exhibited significantly stronger and faster removal performances to the organic pollutants compared with the pure nZVI and pure CSs, in addition to the easy separation from solutions. Typically, in the DDT [or 1, 1, 1‐trichloro‐2, 2‐bis(4‐chlorophenyl)ethane] aqueous solution with 10 ppm, more than 95% of DDT content can be removed within 140 min after adding 1.0 g⋅L −1 nZVI/CSs. The capacity of removal is up to 15.6 mg⋅g −1, remarkably larger than the previously reported one (2.5 mg⋅g −1 ) by carbon nanotubes. This is attributed to the synergistic effects from the CSs' high adsorptivity and nZVI's strong reducibility. This study not only provides a new candidate material for the treatment of the DDT‐polluted environments, but also deepens understanding the process of DDT removal. Abstract : The monodisperse nanostructured zero valent iron/carbon spheres composite (nZVI/CSs) is successfully synthesized by a facile chemical method. The nZVI/CSs has a high specific surface area, a low cost, the environment pollution‐free and the easy separation from solution. It has demonstrated that the nZVI/CSs has excellent removal performances to DDT in the aqueous solution, due to the synergistic effect from reduction of nZVI and adsorption of CSs.